Penggunaan Antibiotik pada ISPA Gambaran Penggunaan Antibiotik pada Anak Dibawah Usia Lima Tahun (Balita) dengan Infeksi Saluran Pernapasan Akut (ISPA) di Puskesmas Kelurahan Tanjung Duren Selatan Tahun 2020-2021: Antibiotik pada ISPA Balita - William William; Axel Thio Wijaya; Donna Mesina Pasaribu; Johannes Hudyono (Jurnal MedScientiae, 2022)
Acute respiratory infections (ARI) is a disease that attacks the respiratory tract with various symptoms. The biggest cause of ARI is a virus (90-95%), so there is no need for antibiotics because most of the causes of ISP are viruses. Irrational administration of antibiotics can lead to bacterial resistance. The purpose of this study was to describe the use of antibiotics in infants under five years of age with ARI at the Tanjung Duren Selatan Village Health Center in the 2020-2021 period. This research was conducted by descriptive observational on 50 subjects. Sampling by consecutive sampling. The results of this study indicate that the majority of ARI patients have cough symptoms (96%) with an age range of 1-3 years (52%) and birth weight < 15 kg (92%). Complete basic immunization status is only 30%. Most of children under five with ARI (80%) did not get antibiotics and as many as 20% of patients under five with ARI used antibiotics, namely amoxicillin. This study concluded that according to the etiology of ARI in children under five caused by a virus, most of the Toddler patients with ARI  not receive antibiotics (80%) and Toddlers who used antibiotics (20%).